Intracranial depth electrodes implantation in the era of image-guided surgery - Ricardo Silva Centeno; Elza Márcia Targas Yacubian; Luis Otávio Sales Ferreira Caboclo; Henrique Carrete Júnior; Sérgio Cavalheiro (Arquivos de Neuro-Psiquiatria)
The advent of modern image-guided surgery has revolutionized depth electrode implantation techniques. Stereoelectroencephalography (SEEG), introduced by Talairach in the 1950s, is an invasive method for three-dimensional analysis on the epileptogenic zone based on the technique of intracranial implantation of depth electrodes. The aim of this article is to discuss the principles of SEEG and their evolution from the Talairach era to the image-guided surgery of today, along with future prospects. Although the general principles of SEEG have remained intact over the years, the implantation of depth electrodes, i.e. the surgical technique that enables this method, has undergone tremendous evolution over the last three decades, due the advent of modern imaging techniques, computer systems and new stereotactic techniques. The use of robotic systems, the constant evolution of imaging and computing techniques and the use of depth electrodes together with microdialysis probes will open up enormous prospects for applying depth electrodes and SEEG both for investigative use and for therapeutic use. Brain stimulation of deep targets and the construction of "smart" electrodes may, in the near future, increase the need to use this method.